Rationalization of Anomalous Pseudocontact Shifts and Their Solvent Dependence in a Series of C-Symmetric Lanthanide Complexes. - Vonci, Michele; Mason, Kevin; Suturina, Elizaveta A.; Frawley, Andrew T.; Worswick, Steven G.; Kuprov, Ilya; Parker, David; McInnes, Eric J. L.; Chilton, Nicholas F. (Journal of the American Chemical Society, 2017)
Bleaney's long-standing theory of magnetic anisotropy has been employed with some success for many decades to explain paramagnetic NMR pseudocontact shifts, and has been the subject of many subsequent approximations. Here, we present a detailed experimental and theoretical investigation accounting for the anomalous solvent dependence of NMR shifts for a series of lanthanide(III) complexes, namely [LnL¹] (Ln = Eu, Tb, Dy, Ho, Er, Tm, and Yb; L¹: 1,4,7-tris[(6-carboxypyridin-2-yl)methyl]-1,4,7-triazacyclononane), taking into account the effect of subtle ligand flexibility on the electronic structure. We show that the anisotropy of the room temperature magnetic susceptibility tensor, which in turn affects the sign and magnitude of the pseudocontact chemical shift, is extremely sensitive to minimal structural changes in the first coordination sphere of L¹. We show that DFT structural optimizations do not give accurate structural models, as assessed by the experimental chemical shifts, and thus we determine a magnetostructural correlation and employ this to evaluate the accurate solution structure for each [LnL¹]. This approach allows us to explain the counterintuitive pseudocontact shift behavior, as well as a striking solvent dependence. These results have important consequences for the analysis and design of novel magnetic resonance shift and optical emission probes that are sensitive to the local solution environment and polarity.